Evaluation Of The Scheduling Of Padangbai-Lembar Ships During The Pandemic Period In Bali Province - Sri Kartini; Dahlia Dewi Apriani; Ayu Diah Prema Widiatmika Dewi (Politeknik Transportasi Sungai Danau dan Penyeberangan Palembang, 2021)
The Padangbai Ferry Port is located in Padangbai Village, Karangasem Regency. This port serves crossings between districts/cities, namely the Padangbai-Nusa Penida cross and between provinces, namely the Padangbai-Lembar cross. As a port that operates 24 hours with 13 trips/day, the current schedule arrangement is very important. Based on the results of a survey conducted by the author, there is a mismatch of the schedule compiled by the Land Transportation Management Center (BPTD) with its implementation, namely the ship's departure time with the existing schedule is not appropriate because the ship is waiting for a full load to depart. To be able to maximize the ship's load, it needs to be supported by a ship schedule that is in accordance with the implementation of the current health protocol in order to create a balance between the number of ships and the existing shipload. Data collection was carried out using the observation method. The data that must be collected are passenger and vehicle productivity, ship characteristics and ship operational time. Institutional methods and library data are taken from the Regional BPTD. XII Province of Bali & NTB. The analysis is carried out by evaluating schedules that are not in accordance with field conditions, and making an appropriate schedule so that no ships still have to wait for passenger and vehicle loads.